Gambaran Pelaksanaan Keselamatan Kesehatan Kerja dan Produktivitas Kerja Petugas Rekam Medis di Rumah Sakit XYZ: Overview of Occupational Health and Safety Implementation and Work Productivity of Medical Record Officers at XYZ Hospital - Zahra Fauziyyah; Fery Fadly (Journal of Health Information Management and Medical Record, 2025)
Hospitals are recognized as high-risk work environments due to the potential for occupational accidents and work-related illnesses. To mitigate these risks, hospitals are required to implement comprehensive Occupational Health and Safety (OHS) programs. Effective implementation of OHS measures not only ensures the safety and well-being of staff but also contributes to increased work productivity. However, in practice, some hospital staff still experience occupational hazards. For instance, medical record staff have reported injuries such as cuts from new medical record folders, and limitations such as cramped workspace conditions, which hinder their performance and reduce overall productivity. This study aims to provide an overview of the implementation of occupational health and safety measures and the work productivity of medical record staff in a hospital setting. This research employed a quantitative descriptive method. Data were collected through questionnaires, direct observations, and documentation review. The implementation of OHS was assessed based on several indicators, including the physical work environment, availability of health facilities, and general health maintenance of workers. The findings revealed that 26 respondents (76%) rated the implementation of occupational health and safety as “good.” In contrast, the assessment of work productivity—measured through indicators such as employee capability, output improvement, work motivation, self-development, work quality, and efficiency—showed that 19 respondents (56%) were categorized as “less productive.”